Age-specific information resources to address the needs of young people with stroke: a scoping review protocol - U. Gopaul; M. Charalambous; S. Thilarajah; L. K. Kwah; S. Chapman; M. Bayley; M. Demers (Systematic Reviews, 2022)
Abstract Background and aims Young people with stroke (YPwS) persistently experience challenges with disability, social reintegration, employment, and financial stability to provide for themselves and their families. The aims of this scoping review are to (1) identify and collate information resources for YPwS and evidence-based self-managements programs and (2) identify gaps in age-specific resources available for YPwS after traditional rehabilitation services have ended and/or who are returning to live in the community. Methods We will include both qualitative and quantitative studies, including all study designs. Participants will be community-dwelling adults aged between 18 and 65 years with a clinical diagnosis of stroke. We will include information resources and evidence-based self-managements programs for YPwS. Search terms will include stroke, young people, and community dwelling. We will search electronic databases such as MEDLINE. The reference lists of included studies, systematic reviews, and stroke guidelines and stroke-specific websites will also be searched. We will also contact Stroke Support Organizations and international/national allied health professional organisations to gather information resources about YPwS. We will also conduct a comprehensive environmental scan of additional resources using the search engine Google. The titles, abstracts, full-text articles, and contents of the resources identified by the search will be assessed against the inclusion and exclusion criteria to identify potentially relevant resources. Results and conclusions Existing resources and self-management programs will be collated and categorized according to the type of needs addressed such as physical, emotions, activities of daily living, information, relationships, and social needs as well as the key gaps identified.